Advocacy for DOHaD research optimizing child kidney health - You-Lin Tain (Pediatrics and Neonatology)
Emerging antenatal risk factors have been associated with an increased risk of kidney disease throughout the offspring's life course. However, the intricate kidney programming mechanisms underlying these risks remain complex and are incompletely understood, but they are rooted in structural and functional alterations within the kidneys. The Developmental Origins of Health and Disease (DOHaD) theory underscores the significance of elucidating core mechanisms initiated through the maternal-fetal interface, which trigger kidney programming. Furthermore, it offers a promising avenue for preventing kidney disease at its earliest stages through a process known as reprogramming. This concise review aims to synthesize existing knowledge regarding the impact of kidney programming on offspring kidney disease and to provide an overview of documented reprogramming strategies as observed in animal models of kidney programming. By consolidating this information, we aim to expedite the translation of research breakthroughs into practical clinical solutions, ultimately resulting in enhanced outcomes for children facing kidney-related issues.